Phenolic-rich jaboticaba (Plinia jaboticaba (Vell.) Berg) extracts prevent high-fat-sucrose diet-induced obesity in C57BL/6 mice. (May 2018) - Moura, Márcio Hércules Caldas; Cunha, Maria Gabriela; Alezandro, Marcela Roquim; Genovese, Maria Inés
Abstract: Obesity has been strongly associated to noncommunicable chronic diseases, and dietary phenolic compounds with reducing the risk of development of these diseases. Sabara jaboticaba ( Plinia jaboticaba ) is an Atlantic Forest native fruit, rich in phenolic compounds, such as ellagitannins proanthocyanidins and anthocyanins. We investigated whether phenolic-rich Sabara jaboticaba extracts (PRJE), with low (LT) or high (HT) tannin concentration can protect C57BL/6 mice from obesity, hyperglycemia, insulin resistance and dyslipidemia induced by high-fat-sucrose diet. Both PRJE, especially the HT extract, prevented the body weight gain while avoiding the white adipose tissues overgrowth. In addition, prevented high fasting blood glucose concentrations and attenuated the hyperinsulinemia. Furthermore, the HT extract prevented high total cholesterol levels. Taken together, our findings confirm that phenolic compounds from Sabara jaboticaba have antiobesity properties and that the tannins play a decisive role in these effects. Graphical abstract: Highlights: Low- and high-tannin phenolic extracts were produced from jaboticaba fruit. The effect of extracts daily administration was evaluated on diet-induced obese mice. Phenolic-rich jaboticaba extracts prevented the excessive gain of body weight. Phenolic-rich jaboticaba extracts improved parameters related to glucose metabolism. Phenolic-rich jaboticaba extracts decreased total cholesterol levels.